IQAC’s Strategic Role in Enhancing OBE, Teaching Quality, Learning Practices, and Curriculum Innovation - Md. Safaet Hossain (Pusat Riset dan Inovasi Nasional Mabadi Iqtishad Al Islami, 2025)
Higher education institutions are experiencing accelerated transformation driven by global competition, technological advancements, and shifting learner expectations. In this context, Internal Quality Assurance Cells (IQACs) serve a strategic role in enhancing teaching quality, strengthening learning processes, and ensuring curriculum relevance through the implementation of Outcome-Based Education (OBE) and pedagogical innovation. This study employs qualitative content analysis by synthesizing theoretical frameworks and recent empirical literature to develop an integrated model of IQAC-led academic transformation. The analysis highlights three key mechanisms: curriculum intelligence systems, pedagogical innovation ecosystems, and comprehensive faculty empowerment. Findings indicate that effective IQACs function not merely as compliance bodies but as catalysts of academic excellence by aligning curriculum with industry needs, fostering continuous faculty development, and promoting technology-enhanced learning and learning analytics. Moreover, phased OBE implementation—comprising capacity building, curriculum redesign, instructional support, and continuous evaluation—significantly strengthens learning outcomes and cultivates reflective academic culture. The proposed framework underscores the interconnected role of curriculum, pedagogy, and faculty capabilities as foundations for institutional excellence. Ultimately, the study affirms that IQACs’ strategic leadership in embedding OBE, leveraging educational technologies, and empowering faculty positions them as pivotal agents in driving sustainable educational transformation.